Transesterification of Jatropha curcas Seed Oil: Reaction Parameters - . Abdelrahman2, Maha; A. Yassin1, Atif A.; Hassan, Ismail; B. Karama, Abdallah; E.S. Mirghani 3, Mohamed (Gezira Journal of Engineering and Applied Sciences, 2019)
This study was carried out to determine the reaction parameters of the fatty acid methyl ester (FAME) and yield produced from Jatropha curcas ( J. curcas ) oil by alkali transesterification. Optimum reaction parameters were observed at 1:6 w/w methanol to oil ratio, 0.5% w/w NaOH to oil molar ratio, 400 rpm agitation speed and 60 ⁰C with resulted in a yield of 99% crude biodiesel and 97.71% FAME.